Mechanotransduction Impairment in Primary Fibroblast Model of Krabbe Disease - Roberta Mezzena; Ambra Del Grosso; Roberto Maria Pellegrino; Husam B. R. Alabed; Carla Emiliani; Ilaria Tonazzini; Marco Cecchini (Biomedicines, 2023)
Krabbe disease (KD) is a genetic disorder caused by the absence of the galactosylceramidase (GALC) functional enzyme. No cure is currently available. Here, we investigate the mechanotransduction process in primary fibroblasts collected from the twitcher mouse, a natural KD murine model. Thanks to mechanotransduction, cells can sense their environment and convert external mechanical stimuli into biochemical signals that result in intracellular changes. In GALC-deficient fibroblasts, we show that focal adhesions (FAs), the protein clusters necessary to adhere and migrate, are increased, and that single-cell migration and wound healing are impaired. We also investigate the involvement of the autophagic process in this framework. We show a dysregulation in the FA turnover: here, the treatment with the autophagy activator rapamycin boosts cell migration and improves the clearance of FAs in GALC-deficient fibroblasts. We propose mechanosensing impairment as a novel potential pathological mechanism in twitcher fibroblasts, and more in general in Krabbe disease.